The Improving Student’s Vocabulary through Rewriting English Song Lyric “The Shawn Mendes Foundation Playlist” - Laveresa, Bayu; Prabowo, AB; Ambarini, Ririn (Institut Agama Islam Sunan Giri Ponorogo, 2024)
The research investigates the efficacy of using English song lyrics, specifically drawn from Shawn Mendes' album